Association between environmental tobacco smoke and depression among Korean women. Issue 6 (22nd June 2015) - Kim, Na Hyun; Kim, Hyeon Chang; Lee, Joo Young; Lee, Ju-Mi; Suh, Il
Abstract : Objective: To evaluate the association between environmental tobacco smoke (ETS) exposure and depression among Korean women. Methods: Between 2008 and 2011, we examined 731 men and 1249 women (aged 39–85 years) for the Korean Genome and Epidemiology Study (KoGES)-Kangwha. Among 1208 never-smoking women, we excluded two women taking antidepressants and five women who did not complete the Beck Depression Inventory (BDI). Therefore, we performed a cross-sectional analysis on 1201 women. ETS exposure was assessed using a self-reported questionnaire, and was classified into three groups: no exposure, occasional exposure and regular exposure. Depression was assessed using the BDI score, which ranged from 0 to 63, and the presence of depression was defined as a BDI score ≥10. Results: Women exposed to ETS were more likely to have depression than those without ETS exposure (p=0.019). When BDI was analysed as a continuous variable, women exposed to ETS had significantly higher BDI scores after full adjustment (overall exposure: β=1.36, p=0.013; occasional exposure: β=1.15, p=0.063; regular exposure: β=1.90, p=0.039). ETS exposure was significantly associated with depression in a dose–response manner even after adjusting for age, body mass index, menopause, socioeconomic status, lifestyle and prevalent chronic diseases. The adjusted OR for depression (95% CI) was 1.72 (1.25 to 2.37) for overall ETS exposure, 1.56 (1.09 to 2.24) for occasional exposure and 2.19 (1.30 to 3.69) for regular exposure, when compared to no exposure. Conclusions: Exposure to ETS was associated with depression among middle aged and elderly Korean women.